Advancements in Medical Device Engineering: Innovative Technologies for Early Diagnosis and Minimally Invasive Treatment - Hameed, Mousa Yaseen; Qambar, Haider Abdul Khaliq; Qader, Mohammed Hayder; Hussein, Ahmed Ayad; Nadhim, Noora Hazim (American Journal of Botany and Bioengineering, 2025)
Advancements in medical device engineering have significantly enhanced early disease diagnosis and minimally invasive treatments, improving patient outcomes and healthcare efficiency. Despite rapid technological progress, challenges remain in optimizing medical devices for accuracy, affordability, and integration with modern healthcare systems. This study reviews innovative medical technologies, including endovascular diagnostic tools, multimodal cancer detection, and intelligent surgical instruments, analyzing their impact on precision medicine. Findings indicate that these innovations enhance diagnostic accuracy, reduce recovery times, and improve treatment effectiveness. The results highlight the importance of interdisciplinary collaboration in medical engineering to drive further advancements, ensuring accessible and cost-effective healthcare solutions. Future research should focus on refining these technologies for widespread clinical adoption and global healthcare improvement.